British North America Acts 1867-1907. Together with other imperial statutes relating to Canada; imperial orders-in-council admitting Rupert's Land, British Columbia, and Prince Edward Island, respectively into the Union; the Manitoba, Alberta, Saskatchewan, Northwest Territories and Yukon acts (Canada) with various amending acts; - Canada. (Ottawa : C.H. Parmelee, 1913)
Mode of access: Internet.